Preventing Youth Access to Tobacco. - Pokorny, Steven B. (Taylor and Francis, 2014)
Learn to develop and assess comprehensive youth tobacco interventions!Preventing Youth Access to Tobacco examines the components of a preventive public health intervention directed at reducing the rate of youth tobacco use. This valuable book describes this innovative intervention, which involves making tobacco more difficult for young people to acquire and also calls for fines for possession of tobacco. It illustrates the rationale for this intervention and reviews the literature on the topic, pointing to findings that indicate that this kind of comprehensive intervention has been s.